Music. An appreciation - Kamien, Roger (Boston : McGraw-Hill, 2000)
Elements - Sound - Rhythm - Melody - Harmony - Key - Musical form - Style ; Middle Ages - Renaissance - Baroque period - Classical period - Romantic period - Twentieth century - Jazz - American musical - Rock - Nonwestern music.
Includes bibliographical references (p. 697-698) and index.
Keywords: Music appreciation